Energy Conservation Behaviour Among the Malaysian Youth: A Study Under the Premises of Value-Belief-Norm Model - Al Mamun, Abdullah; Hayat, Naeem; Masud, Muhammad Mehedi; Yang, Qing; Salameh, Anas A.; Salleh, Mohd Fairuz Md. (Frontiers in Energy Research, 2022)
Intensive energy consumption has become a norm among the younger generation. Energy consumption can be reduced when consumers develop environmental values, beliefs, and norms to build pro-environmental behaviours. The current study’s objective is to expose the intention and behaviour to minimise energy consumption among young Malaysian residents using the value-belief-norm (VBN) framework. Data collection was performed using social media in a cross-sectional manner. The collected data were analysed using partial least squares structural equation modelling (PLS-SEM) and necessary condition analysis (NCA). Data analysis confirmed the application of VBN framework on the energy conservation behaviours among Malaysian youth. Personal biospheric and altruistic values significantly saturated the new environmental paradigm that harnessed the awareness of consequences and ascription of responsibility to engage in pro-environmental behaviours. The personal norms significantly influenced the energy conservation intention, leading to energy conservation behaviours. The NCA results suggest that the ascription of responsibility, biospheric and altruistic values are the most significant necessary conditions for promoting energy conservation behaviours. The policy and practical implications have revealed that collaborative efforts are required to address the issue of wasteful energy consumption at a personal level, promote energy-efficient household devices, and increase monetary nudges to reward energy conservation behaviours. The study limitations and future research openings are also discussed in this paper.